El culto imperial en el Conventus Asturum - Rabanal Alonso, Manuel Abilio (Estudios humanísticos. Geografía, historia y arte, 1997)
The cult of the emperor is a cornerstone of the official Roman religion. Hispania played a pioneering role in this field from the beginning of the Roman Empire. This circumstance is a clear step in the process of acculturation we usually know as Romanization.